Flame‐retardant, thermal and mechanical properties of PLA/ramie fiber composites. Issue 7 (25th April 2022) - Zhan, Jianghu; Wang, Jiachang; Lin, Jun; Zhao, Guoqun; Ji, Shengcheng; Li, Xiaoling; Li, Jiao; Wang, Guilong; Chen, Liang; Guan, Yanjin; Naceur, Hakim
Abstract: Although the natural fiber composites are preferable for sustainable and green product due to the environmental friendliness, they suffer from the high flammability. In this study, the flame retardant ramie fiber reinforced poly(lactic acid) composites were prepared and the synergistic barrier effect of aluminum diethylphosphinate, melamine cyanurate and silica was investigated. When the mass ratio of each flame retardant was 10%, the composites reached UL‐94 V0 rating with the limiting oxygen index of 30.1%. The excellent flame retardancy was resulted from the formation of high‐quality char layers, the chain reaction of free radicals as well as the dilute effect of inert gases generated during the combustion process. Besides, the cone calorimeter test showed that the peak heat release rate and total heat release decreased by 22.5% and 15.0%, respectively. Importantly, the flame retardants did not deteriorate the mechanical properties, thanks to the fiber reinforcement and high‐adhesion work between the flame retardants and the matrix which was demonstrated by the contact angle test.